Relative Effect of Food Supplementation and Natural Resources on Female Red Deer Distribution in a Mediterranean Ecosystem - Pérez-González, Javier; Barbosa, a Márcia; Carranza, Juan; Torres-Porras, Jerónimo (Journal of Wildlife Management, 2010)
Supplementary feeding is a widespread game management practice in several red deer (Cervus elaphus) populations, with important potential consequences on the biology of this species. In Mediterranean ecosystems food supplementation occurs in the rutting period, when it may change mating system characteristics. We studied the role of food supplementation relative to natural resources in the spatial distribution, aggregation, and mean harem size of females in Iberian red deer (Cervus elaphus hispanicus) during the rut. We studied 30 red deer populations of southwestern Spain, 63% of which experienced supplementary feeding. Using multivariate spatial analyses we found that food supplementation affected distribution of females in 95% of the populations in which it occurred. Green meadows present during the mating season acted as an important natural resource influencing female distribution. Additionally, the level of female aggregation and mean harem size were significantly higher in those populations in which food supplementation determined female distribution than in populations in which female distribution did not depend on supplementary feeding. Because female aggregation and mean harem size are key elements in sexual selection, supplementary feeding may constitute an important anthropogenic element with potential evolutionary implications for populations of Iberian red deer.
Keywords: cervus elaphus; environmental resources; female aggregation; mating system; Mediterranean ecosystems; spatial analyses

The composition of the diet of red deer (Cervus elaphus) in a Mediterranean environment: a case of summer nutritional constraint? - Bugalho, Miguel N; Milne, John a (Forest Ecology and Management, 2003)
The composition of the diet of red deer (Cervus elaphus) in a Mediterranean environment, in southern Portugal, was estimated during summer 1995–1997 using n-alkane analysis. Standing crop of herbage layer biomass was estimated between June and September 1995–1997 using the clipping quadrat method. There was a large variability between years in the availability of the herbage layer biomass. Biomass was three fold greater and availability of legumes higher in a wet than in a dry year. Live green material was available in the herbage layer in June, but not thereafter, even during a wet year. Red deer ingested a higher proportion of browse in summer during drier years (0.83–0.89) than during a wet year (0.47). In the drier years, the herbage layer was replaced in the diet by browse species that were uneaten in the wet year. Contrary to Atlantic environments, where red deer include a large proportion of browse in their diets during winter, summer is likely to be a season of nutritional constraint for red deer inhabiting Mediterranean environments
Keywords: browse; cervus elaphus; diet composition; Mediterranean

The composition of the diet of red deer (Cervus elaphus) in a Mediterranean environment: a case of summer nutritional constraint? - Bugalho, Miguel N.; Milne, John a (Forest Ecology and Management, 2003)
The composition of the diet of red deer (Cervus elaphus) in a Mediterranean environment, in southern Portugal, was estimated during summer 1995–1997 using n-alkane analysis. Standing crop of herbage layer biomass was estimated between June and September 1995–1997 using the clipping quadrat method. There was a large variability between years in the availability of the herbage layer biomass. Biomass was three fold greater and availability of legumes higher in a wet than in a dry year. Live green material was available in the herbage layer in June, but not thereafter, even during a wet year. Red deer ingested a higher proportion of browse in summer during drier years (0.83–0.89) than during a wet year (0.47). In the drier years, the herbage layer was replaced in the diet by browse species that were uneaten in the wet year. Contrary to Atlantic environments, where red deer include a large proportion of browse in their diets during winter, summer is likely to be a season of nutritional constraint for red deer inhabiting Mediterranean environments
Keywords: browse; cervus elaphus; diet composition; Mediterranean

The foraging ecology of red deer (Cervus elaphus) in a Mediterranean environment: is a larger body size advantageous? - Bugalho, M. N.; Milne, J. a; Racey, P. a (Journal of Zoology, 2001)
In Mediterranean environments browse is expected to be a major component of the diet of red deer Cervus elaphus during the summer when most grasses senesce. In this study the hypothesis is tested that, if browse is an essential food resource at this time, the sex with the larger body size may have a greater physical ability to reach the tree canopy and include a higher proportion of browse in its diet. The organic matter digestibility (OMD) and composition of the diet of a population of red deer males and females were measured between July and September, in 1996 and 1997, in an area of Portugal with a Mediterranean type of climate, using the n-alkane technique. Direct observations of animals browsing on tree canopies and shrubs were made also during the same period. The OMD of the diet was signi®cantly different between sexes and between years and was higher in males than females both in 1996 (means sem for males and females, 0.65 and 0.58 0.026, respectively) and 1997 (means for males and females, 0.59 and 0.48 0.045, respectively). The proportion of cork oak Quercus suber in the diet was also signi®cantly different between sexes and between years, with males having a higher proportion of cork oak in their diets in 1996 (males and females, 0.30 and 0.16 0.037, respectively) and 1997 (males and females, 0.41 and 0.23 0.064, respectively). A signi®cantly lower proportion of the herbage layer was found in the diet of males in 1996 (males and females, 0.46 and 0.64 0.048) but not in 1997. The number of observations of males browsing on tree canopies was signi®cantly higher than females. It is concluded that there are differences between sexes in the composition and quality of the diet and that a larger body size may confer advantages in situations where browse is an essential food resource.
Keywords: body-size; browse; cervus elaphus; diet composition; Mediterranean

The foraging ecology of red deer (Cervus elaphus) in a Mediterranean environment: is a larger body size advantageous? - Bugalho, M N; Milne, J a.; Racey, P a. (Journal of Zoology, 2001)
In Mediterranean environments browse is expected to be a major component of the diet of red deer Cervus elaphus during the summer when most grasses senesce. In this study the hypothesis is tested that, if browse is an essential food resource at this time, the sex with the larger body size may have a greater physical ability to reach the tree canopy and include a higher proportion of browse in its diet. The organic matter digestibility (OMD) and composition of the diet of a population of red deer males and females were measured between July and September, in 1996 and 1997, in an area of Portugal with a Mediterranean type of climate, using the n-alkane technique. Direct observations of animals browsing on tree canopies and shrubs were made also during the same period. The OMD of the diet was signi®cantly different between sexes and between years and was higher in males than females both in 1996 (means sem for males and females, 0.65 and 0.58 0.026, respectively) and 1997 (means for males and females, 0.59 and 0.48 0.045, respectively). The proportion of cork oak Quercus suber in the diet was also signi®cantly different between sexes and between years, with males having a higher proportion of cork oak in their diets in 1996 (males and females, 0.30 and 0.16 0.037, respectively) and 1997 (males and females, 0.41 and 0.23 0.064, respectively). A signi®cantly lower proportion of the herbage layer was found in the diet of males in 1996 (males and females, 0.46 and 0.64 0.048) but not in 1997. The number of observations of males browsing on tree canopies was signi®cantly higher than females. It is concluded that there are differences between sexes in the composition and quality of the diet and that a larger body size may confer advantages in situations where browse is an essential food resource.
Keywords: body-size; browse; cervus elaphus; diet composition; Mediterranean

HABITAT PREFERENCE OF SPANISH IBEX AND OTHER UNGULATES IN SIERRAS DE CAZORLA Y SEGURA (SPAIN) - ESCOS, J.; Alados, C. L. (MAMMALIA, 1992)
Studied the habitat preference in Autumn and Spring periods of Spanish ibex (Capra pyrenaica), fallow deer (Dama dama) and red deer (Cervus elaphus) in the Sierras de Cazorla y Segura Park (Spain). Spanish ibex occupied most altitude range studied, especially highest parts and avoiding areas below 800 m, red deer selected lowest elevations between 700 to 1100 m and fallow deer (between 1200-1600 m) occupied an intermediate annual altitudinal range. All the ungulates studied showed, except the red deer populations, a descent of altitudinal levels in the Spring period. Ibex used more covered areas specially females and young in Spring period, fallow deer occupied open habitats and red deer preferred holm-oak woods. In general terms the rut occurred in more open areas while in the birth season, females and young especially occupied covered areas. According to the overlap index (Pianka 1973) ibex with fallow deer could get a high risk of competition, while Spanish ibex and red deer, the only endemic species show the lowest level of overlapping on the resources studied. Segregation of the sexes studied in different habitats was observed. In Autumn, Spanish ibex and fallow deer showed a tendency to occupy sunny areas at dawn and dusk and this tendency occurred in red deer only at dawn but not at dusk. However in Spring, Spanish ibex, fallow and red deer occupied sunny slopes at dusk but only fallow deer do so at dawn.
The following values have no corresponding Zotero field: pub-location: 55 RUE DE BUFFON, 75005 PARIS, FRANCE publisher: MUSEUM NAT HIST NATURELLE
Keywords: APS; Capra pyrenaica; cervus elaphus; Dama dama; habitat prefference; Holm oak; Spain; ungulates